Isocrates: Writer or Rhetor? Remarks about the Composition of the "Panegyricus" - Janik, Joanna (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2016)
The combination of written and oral styles remains one of the most striking features of Isocrates’ work; the purpose of this article is to present a general outline of this phenomenon in Panegyricus.
Keywords: Isocrates; textuality; orality; rhetoric